2012
DOI: 10.1182/blood-2011-04-346619
|View full text |Cite
|
Sign up to set email alerts
|

A novel lentiviral vector targets gene transfer into human hematopoietic stem cells in marrow from patients with bone marrow failure syndrome and in vivo in humanized mice

Abstract: In vivo lentiviral vector (LV)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…In agreement with previous reports [52][53][54], we observed that the transduction efficiency of human MSCs is higher than HSCs; with 90% and 25% of cells transduced respectively. In line with the greater transduction efficiency of MSCs, they over-expressed all MPS enzymes tested to a greater extent than HSCs.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with previous reports [52][53][54], we observed that the transduction efficiency of human MSCs is higher than HSCs; with 90% and 25% of cells transduced respectively. In line with the greater transduction efficiency of MSCs, they over-expressed all MPS enzymes tested to a greater extent than HSCs.…”
Section: Discussionsupporting
confidence: 94%
“…Importantly, the H/F-LVs were able to efficiently transduce unstimulated hCD34 1 cells at levels not reported before (40% to 70%) after a single exposure at low vector doses (MOI, 10; Figure 2A). As we previously described, 12,42,43 the VSV-G-LVs were unable to transduce efficiently resting hCD34 1 cells (Figure 2A). In contrast to cytokine-prestimulated hCD34 1 cells, their resting counterparts require at least an MOI of 10 for efficient H/F-LV transduction ( Figure 1E-F vs Figure 2B).…”
Section: Conditioning and Reconstitution Of Nsg Micementioning
confidence: 95%
“…Given the improvement of cell culture conditions, 45 lentiviral vectors, 46 and transduction protocols, 47,48 as well as the progress made in the field of RNAi-based therapeutics, 49 we envision that RNAi screens could assist therapeutic decisions in AML in the future (supplemental Figure 14). We therefore believe that our results should encourage the further development of this technology.…”
Section: Discussionmentioning
confidence: 99%